ASSESSMENT OF CLIMATE VULNERABILITY AS A COMPONENT OF PLANNING MEASURES FOR ADAPTATION TO CLIMATE CHANGE (Proceedings of the YSU C: Geological and Geographical Sciences, 2024)
The definition of the concept of climate vulnerability is given, extreme indices are determined and an assessment of the climatic vulnerability of the territory of Belarus based on dimensionless indices is presented. The observation period covers 1989–2022, the period of climate warming. The spatial and temporal patterns of the distribution of meteorological quantities determining climatic vulnerability in the territory of Belarus are considered. The obtained index values can be used in long-term planning of adaptation measures to climate change.
Keywords: climate; climate vulnerability; climate indices; temperature; precipitation; wind